Food insecurity and coping strategies and their association with anxiety and depression: a nationally representative South African survey. Issue 4 (24th April 2023) - Dlamini, Siphiwe N; Craig, Ashleigh; Mtintsilana, Asanda; Mapanga, Witness; Du Toit, Justin; Ware, Lisa J; Norris, Shane A
Abstract: Objective: To investigate food insecurity and related coping strategies among South African households and their associations with anxiety and depression. Design: Cross-sectional study. Food insecurity and coping strategies were assessed using a modified Community Childhood Hunger Identification Project and the Coping Strategies Index questionnaires. The Generalized Anxiety Disorder-7 and Patient Health Questionnaire-9 were used to assess anxiety and depression risk. Ordered logistic regressions were used to test associations of food insecurity and related coping strategies with anxiety and depression. Setting: South Africa during COVID-19, October 2021. Participants: Nationally representative sample of 3402 adults, weighted to 39, 640, 674 South African households. Results: About 20·4 % of South African households were food insecure, with the most affected being from the lowest socio-economic groups. Shifting from 'food secure' to 'at risk' or from 'at risk' to 'food insecure' group was associated with 1·7 times greater odds of being in a higher category of anxiety or depression ( P < 0·001). All coping strategies were used to some extent in South African households, with 46·0 % relying on less preferred and less expensive foods and 20·9 % sending a household member to beg for food. These coping strategies were mostly used by food-insecure households. Although the odds of moving to a higher category of anxiety and depression were observed among all coping strategies (all P < 0·001), begging for food was associated with the highest odds (OR = 2·3). Conclusions: Food insecurity remains a major health threat in South Africa. Public measures to address mental health should consider reductions in food insecurity as part of their strategy.